Computed Tomography Analysis of the Manufacture of Cast Head-Bust Figurines by Patricia ‘Pat’ Elvins (1922–2011) - Dirk H. R. Spennemann; Clare L. Singh (Heritage, 2023)
The Alice Springs sculptor Patricia Elvins created a number of busts of Indigenous Australian men, women, and children, which were distributed as casts for the gift and souvenir market. Produced between the early-1960s and the early-1990s, these varnished casts exist with four different artists’ signatures, representing collaboration with different production potters who produced the casts. Macroscopic analysis shows significant differences in weight between casts of the same bust. CT scanning was carried out to understand the make-up of these casts and to illuminate differences in production techniques. The scanning revealed that all figurines were cast, but that casting techniques varied not only between production potters but also among figurines of the same potter. It revealed differences in the densities of the casting material, both between and within specimens, suggesting that production was not standardized but occurred in smaller batches, possibly on demand of low-volume sales stock. The study has shown the potential of non-destructive CT scanning to go beyond this and serve as a tool to examine the casting process itself as well as to contribute to an understanding of the nature of the plasters used.